THE EFFECT OF WORK DISCIPLINE AND WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE THROUGH JOB SATISFACTION IN THE TAMALANREA DISTRICT OFFICE, MAKASSAR CITY - Uhud Darmawan Natsir; Siti Nur Faidah; Nurul Fadilah Aswar (Jurnal Manajemen, 2026)
Abstract: This study aims to analyze the influence of work discipline and work environment on employee performance with job satisfaction as an intervening variable at the Tamalanrea District Office, Makassar City. This study uses a quantitative approach with a survey method. Data were collected by distributing questionnaires to 32 employees. The data analysis technique used Structural Equation Modeling–Partial Least Square (SEM-PLS) with the help of SmartPLS. The results showed that work discipline had no significant effect on job satisfaction or employee performance. On the contrary, the work environment had a positive and significant effect on job satisfaction and employee performance. Job satisfaction also had a positive and significant effect on employee performance. In addition, job satisfaction did not mediate the effect of work discipline on employee performance, but was able to significantly mediate the effect of the work environment on employee performance.Keywords: Work discipline, work environment, job satisfaction, employee performance